Legal Certainty in the Division of Joint Property after Divorce - Firayani Firayani (Leges Privatae, 2024)
This study aims to analyze the legal certainty in the distribution of joint property after divorce, with an emphasis on the challenges faced in the implementation of the law in Indonesia. The division of joint property is a crucial issue in the context of divorce which often causes disputes between former spouses, where the principles of justice and equality should take precedence. In this study, a normative juridical approach is used to examine laws and regulations, legal doctrines, and court decisions related to the division of common property, with a focus on Law Number 1 of 1974 concerning Marriage and the Civil Code. The results show that despite the legal provisions governing the division of common property, its implementation is often hampered by various factors, including differences in interpretation among judges, the existence of cultural values that influence decisions, and technical obstacles in asset valuation. Variations in court decisions create legal uncertainty that not only harms one party, but also impacts the welfare of children involved in divorce. Uncertainty about the rights and obligations of each party has the potential to cause prolonged conflicts and harm all parties. As part of the analysis, the study also highlights the social and economic impact of legal uncertainty in the distribution of assets, especially for the financially weaker parties. To improve fairness and certainty in the division of common property, this study recommends the need for more detailed and uniform guidelines in court decision-making procedures, as well as harmonization between national and local regulations. Thus, it is hoped that the process of distributing joint property after divorce can be carried out in a fairer, more efficient, and transparent manner, so that the interests of all parties, especially children, can be well protected.